Co-based nanowire films as complementary hydrogen- and oxygen-evolving electrocatalysts in neutral electrolyte. Issue 13 (5th June 2017) - Zhang, Ling; Xie, Lisi; Ma, Min; Qu, Fengli; Du, Gu; Asiri, Abdullah M.; Chen, Liang; Sun, Xuping
Abstract : The Co2 N nanowire film on a Ti mesh (Co2 N/TM) and Co-phosphate nanowire film on a Ti mesh (Co–Pi/TM) act as complementary water-splitting electrocatalysts with strong durability in 1.0 M PBS, affording 10 mA cm −2 at 1.78 V. Abstract : Designing and developing non-noble-metal electrocatalysts for efficient full water splitting at neutral pH is highly desired but still remains a huge challenge. In this communication, we report the development of homologous Co-based nanowire films, Co2 N nanowire film on a Ti mesh (Co2 N/TM) and Co-phosphate nanowire film on a Ti mesh (Co–Pi/TM), as complementary catalysts for stable electrochemical hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in neutral electrolyte. Co2 N/TM shows remarkable HER activity with the need of an overpotential of 290 mV to drive 10 mA cm −2 in 1.0 M phosphate-buffered saline (PBS), and Co–Pi/TM is superior in OER activity affording 10 mA cm −2 at overpotentials of only 430 and 300 mV in 0.1 and 1.0 M PBS, respectively. The two-electrode water electrolyzer using Co2 N/TM as a cathode and Co–Pi/TM as an anode affords a water-splitting current density of 10 mA cm −2 at a cell voltage of 1.78 V with 100% Faradaic efficiency in 1.0 M PBS, promising the practical uses of such homologous Co-based catalyst materials in technological devices.